Penetration and performance testing of the HP³ Mole for the InSight Mars mission. (February 2020) - Wippermann, T.; Hudson, T.L.; Spohn, T.; Witte, L.; Scharringhausen, M.; Tsakyridis, G.; Fittock, M.; Krömer, O.; Hense, S.; Grott, M.; Knollenberg, J.; Lichtenheldt, R.
Abstract: During the development and the qualification of the Heat Flow Physical Properties Package (HP³) instrument (developed by the German Aerospace Center), which is part of the NASA Mars mission InSight, its self-propelling subsurface probe, the HP³ Mole was used in several penetration tests. Here, the performance of the Mole to reach the target depth, to avoid or overcome obstacles on its path, and its directional stability in the subsurface is elaborated. The different test beds and set ups are described and the results are presented. The deep penetration tests (DPT), with the purpose to reach the target depth, are the most important performance tests and therefore the results are investigated in more detail in section 2. Full functional tests (FFT), which showed the performance and degradation of the mechanism inside the Mole, are presented in section 3. Additional penetration and life cycle tests are described in section 4. The testing has demonstrated that the HP³ Mole meets all of its penetration requirements with margin. Highlights: Compilation of pre-flight performance test data of HP³ Mole on Mars mission InSight. HP³ Mole capable to penetrate up to 5 m in simulant soils in ambient conditions. Restricted performance for high cohesive soils in low pressure environment. Durability and stable performance confirmed in functional and life testing.